PENGARUH BIMBINGAN SOSIAL TERHADAP ETIKA PERGAULAN PESERTA DIDIK KELAS VII SMP - Nur Afiddin, Wahidatul; Wicaksono, Luhur; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study discusses the influence of social guidance on the ethics of social interaction among 7th grade students of SMP Negeri 04 Sungai Raya in 2019. Ethics in relationships that must be possessed by adolescents is respecting fellow students, respecting ideas, thoughts and opinions of others, daring to convey something, expressing opinions politely, get used to saying thank you, dare to admit mistakes, civilized and respect older people. In providing assistance to deal with students' social ethical issues, social assistance can be carried out. This is a survey research with a descriptive method using a quantitative approach. The population in this study were 35 7th grade students of SMP Negeri 04 Sungai Raya in 2019. Data were collected using indirect communication techniques and the data collection tool was a questionnaire. The findings show that the percentage of social guidance is 72% and social ethics is 74%. Therefore, it is concluded that there is a positive and significant influence between social guidance and the ethics of social interaction for Grade VII students of SMP Negeri 04 Sungai Raya. This means that the better the social guidance provided by the supervisor, the better the students' social ethics. Conversely the more social guidance is not given properly, the lower the social ethics of students.Â Keywords: Social guidance,Â  Social ethics